Naming Strategies In Modern Standard Arabic Online News Discourse: The Case Of Al-Jazeera And BBC Coverage On The 2011 Tunisian Jasmine Revolution - Muhammad Marwan Ismail; Farah Nadia Harun; Anissa Daoudi (Global Business and Social Entrepreneurship Sdn Bhd, 2024)
Volume 4: No: 11